Localization of feminist translation in China : a case study of Lin Yutang’s translation of Fu Sheng Liu Ji - Chen, Zhuo (2019)
The 20th century witnessed the successive upsurges of feminist movements on the European and North American land. The in-depth reflection of feminists upon gender issues has also given birth to feminist thoughts which are still influential today on women’s lifestyle and way of thinking. When feminist thoughts were introduced to the translation field, new forefront was opened for translators to reinvestigate the gendered nature of language and women’s role in the translation process. Feminist translation studies and practices, thereby, have achieved vigorous development in the west. However, the development of feminist translation in China has been retarded as compared with that in the west after it was introduced. Researchers in this field tended to focus their attention on the review of western feminist translation theories or the study of the Chinese translation of feminist literature in English. Few have claimed to be a feminist translator and conducted relative practices. In this dissertation, the author attempts to explore the reason behind this dilemma and put forward tentative solutions. By carrying out a case study on Lin Yutang’s translation of Fu Sheng Liu Ji (浮生六记), a Chinese classic known for its detailed and vivid depiction of traditional Chinese women, the author explores how Lin, as a Chinese translator, process gender issues and construct Chinese female image under the guidance of his unique feminist ideology in his translation. The author aspires to draw enlightenment from Lin’s case to add new perspectives to feminist translation studies and practices in China and facilitate the localization of this translation genre in its unique cultural context.